Etika Santri di Pesantren Al-fath dalam Prespektif Etika Plato - Rohman, Ahmad Yani Fathur; Ismaning Ayu, Qurrotun A’yunnisa (Abrahamic Religions: Jurnal Studi Agama-Agama, 2023)
This research aims to examine the ethics of students (santri) at Al-Fath Student Islamic Boarding School from the perspective of Plato's ethics. Al-Fath Islamic Boarding School is located near the campus of the State Islamic Institute (IAIN) in Kediri, and it specifically admits female students, the majority of whom are IAIN Kediri students. This study employs a qualitative method with a descriptive approach involving a literature review and historical reflection. The study showed that the ethics or moral values observed in the students of Al-Fath Islamic Boarding School share similarities with Plato's ethical teachings. Plato's ethical philosophy emphasizes virtues as its core doctrine, with a focus on how individuals can attain a higher level of virtue through the cultivation of the soul and an understanding of the essence of the world, which is largely a shadow of the world of ideas. The foundation of Plato's ethics is his love for the Supreme Good, which, in the context of this boarding school, refers to God as the ultimate reality. Al-Fath Student Islamic Boarding School has a vision that encompasses morality, knowledge, and active participation in society, with morality or ethics as the primary goal of education, supported by knowledge and an active role in society. Allah, as the God of the universe, serves as the foundation and ultimate goal in achieving happiness through ethical conduct, aligning with Plato's ethical teachings that lead to the Supreme Good.AbstrakArtikel ini bertujuan untuk mengkaji etika santri di Pesantren Pelajar Al-Fath dengan perspektif etika Plato. Pesantren Al-Fath terletak di sekitar kampus Institut Agama Islam Negeri (IAIN) Kediri dan secara khusus menerima santriwati, yang sebagian besar merupakan mahasiswi IAIN Kediri. Kajian ini  menggunakan metode kualitatif dengan pendekatan deskriptif model studi literatur dan refleksi historis. Hasil penelitian menunjukkan bahwa etika atau akhlak yang diamati pada santri Pesantren Pelajar Al-Fath memiliki kesamaan dengan ajaran etika Plato. Ajaran etika Plato menekankan keutamaan sebagai inti ajaran, dengan penekanan pada bagaimana manusia dapat mencapai derajat yang tinggi melalui proses latihan jiwa dan kesadaran tentang hakikat dunia ini yang sebagian besar merupakan bayang-bayang dari dunia ide. Landasan etika Plato adalah cinta kepada Sang Baik, yang dalam konteks pesantren ini, merujuk kepada Tuhan sebagai realitas tertinggi. Pesantren Pelajar Al-Fath memiliki visi yang mencakup berakhlak, berilmu, dan berperan, dengan akhlak atau etika sebagai tujuan utama dalam pendidikan, didukung oleh pengetahuan dan peran aktif dalam masyarakat. Allah sebagai Tuhan semesta alam adalah landasan dan tujuan utama dalam mencapai kebahagian melalui berakhlak, seiring dengan ajaran etika Plato yang mengarah kepada Sang Maha Baik.